PENGEMBANGAN PHANTOM ULTRASOUND DENGAN VISKOSITAS DIMODIFIKASI UNTUK MENIRU JARINGAN LUNAK MANUSIA - Muhammad Ulin Nuha ABA, M.Si; Abdul Haris Kuspranoto; Mugiyanto .; Syaikhul Hadi; Christopher Nicolaus Satrio Anggono; Gus Ahmad ilham (MEDIKA TRADA, 2026)
The diagnostic accuracy and success of ultrasound-based intervention procedures depend heavily on the quality of device calibration and the expertise of medical personnel. The development of ultrasound phantoms that can realistically replicate the acoustic and mechanical properties of human soft tissue is a crucial requirement in medical education and the standardisation of electromedical technology. This study aims to develop and evaluate a method for producing soft tissue USG phantoms with modified viscosity and elasticity using polyvinyl alcohol (PVA) material, as well as integrating 3D printing technology to achieve anatomical accuracy. The phantoms were developed using a mixture of low and high viscosity PVA variants with the addition of ethylene glycol as a freeze-protectant. The fabrication process was carried out through a strictly controlled freeze-thaw cycle to manipulate the shear modulus and viscosity separately. Characterisation was performed through longitudinal sound velocity measurements (frequency 5–20 MHz), microstructure evaluation with a scanning electron microscope (SEM), and viscoelastic property testing using shear wave viscoelastography based on the Kelvin-Voigt model. The results show that the use of cryoprotectant produces a more homogeneous microstructure with a shear modulus of approximately 2.17 kPa and a viscosity of approximately 2.0 Pa · s, which is close to the physiological characteristics of human soft tissue. Acoustic parameters showed a sound velocity ranging from 1510–1571 m/s with an attenuation exponent of 1.23–1.38 dB/cm/MHz, meeting clinical range standards. The integration of natural fibres into the bio-elastomer matrix successfully created anisotropic properties resembling fibrous tissues such as muscle. The independent viscosity modification approach and the use of additive manufacturing provide a flexible platform for producing high- precision ultrasonic phantoms. This innovation supports the development of standardised and safe clinical intervention training tools, as well as reliable calibration instruments for the development of future imaging techniques such as elastography. Keywords: Ultrasonic Phantom, viscosity, PVA, 3D Printing, Medical Calibration.